Reformasi Birokrasi dan Gejala Masyarakat Prismatis (Studi Penempatan Pegawai pada Wilayah Kecamatan Wara Timur, Kota Palopo) - Kambau, Andi Molang Chaerul; Sunarding, Sunarding; Harun, Harsya (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2022)
The study aims to discover and figure out the extent of the implementation of bureaucratic reform, in terms of organizational and of human resources dimentions, and whether it still has a strong prismatic society tendency. In the context, the dominant indication in staffing is the formalistic stigma, especially placement of the apparatus. The method is a survey through area sampling technique. Kecamatan Wara Timur was chosen because the area has the most urban villages, has the largest population in Palopo City. The results showed that the implementation of bureaucratic reform by menas of organizational change indicated by the presence of vacant 5th, 6th, and 7th class positions, while the hardware, The Mayor Regulation 35/2019 as regards Position Levels, had been established. These also indicates that the prismatic society in local government organizations is still quite strong.